The importance of the Dental Surgeon in the Intensive Care Unit (ICU): An analysis of the contribution of oral health to the integrated treatment of critically ill patients (Research, Society and Development, 2023)
Introduction: The Intensive Care Unit is an area aimed at the most weakened and care-dependent patients. The work of a multidisciplinary team in this hospital environment is of great importance, taking into account the patient's critical health status, the integration of a Dental Surgeon into this team is considerable. Objective: To highlight and describe the importance of the role of the dental surgeon in the multidisciplinary team in the Intensive Care Unit (ICU). Methodology: A literature review was carried out on the importance of the dental surgeon in the intensive care unit (ICU), through analysis of the periodic database: CAPES, Pubmed, LILACS and SciELO, according to inclusion and exclusion criteria. Discussion: It highlights the importance of there being an agreement between professionals on the need to provide dental care, from the simplest, such as hygiene measures that result in the prevention of oral changes, to the most invasive procedures. Conclusion: Dental treatment within this hospital environment is essential, aiming for better basic conditions for the patient's health and well-being.